Isolation and detection of Pasteurella multocida from clinical hemorrhagic septicaemia cases of buffaloes (Indian Journal of Veterinary Pathology, 2025)
Hemorrhagic septicaemia (HS) is an economically important disease of livestock affecting various species of animals. The present investigation was conducted to detect and isolate the causative organism from the HS suspected cases of the buffaloes in two different outbreaks. Total 24 samples (14 nasal swabs, 6 lung swabs and 4 blood samples) from the suspected HS cases were processed for the bacterial isolation and DNA was extracted for PCR detection. Culture and biochemical assays from two samples showed characteristics of the Pasteurella multocida organism. The KMT1 gene was targeted as the marker gene for P. multocida for the PCR assay confirmation. Out of 24 samples, four were confirmed to be positive for P. multocida. In conclusions, P. multocida associated respiratory illness was common in buffaloes during stressful climatic conditions and to minimize the spread, the animal owners should ensure appropriate medication, vaccination programs and good hygienic practices in crowded areas.